(Qualitative study indifferentiation of ratio and weights of meat,bones, skinIn local meatand eggs chickens (Journal of the College of Basic Education, 2022)
The present study was carried out at Science Department , College of Basic education / University offal- Mustansiryah from period 15-11-2021 to 15-3-2022. The objective of this study was to improved effects of species and race in weights of meat , bones , skin ,from the whole weight of chicken . A total of 48 ISA Brownand white (luhman ) strain hens at 8 months of age were used with level weight (1300 gm, 1400 gm, 1500 gm ).distributed in 5repeated in each one 2 chickens .All Hens were raised in cages (2 hens / cage).The results can be summarized as follow as :. high mean value was shwoen in meat chicken at (1500gm weight ) reached to (190.5 gm ) with ratio (12.7 %)there was significant difference in (p<0.01 ) and high level of value of skin in egges chicken reached to (300gm )with ratio (20%)there was significant difference in (p<0.01 ) .The result of meat value reached in meat chicken to(994.25 gm)with ratio( 66.28 %) in weight 1500 gmwith ratio (66.28 %) and in same weight of egges chickens was reached to( 709 gm) with ratio( 47.26%). Also we found approximation of bone weight in local meat chickens in all weight was taken , that was sequence in ( 267.5 gm ¸ 263.5gm ¸247,75 gm ) there was significant difference in (p<0.01 )in value of weight of bones in all weights was taken and there were increase of weight of meatwith high ratio in whole weight, on the other hand eggs chicken were steedy with high weight in bones and skin ratio that’s the reason behind of consumers did not like this type of chicken in eating .The skin in meat chicken was increased in weight with increased in whole weight of chicken was taken we noticed the weight of skin in eggs chicken high than meat chicken in same weight ,this is due to type of race and physiological of chickens like as activity and high temperature.